Ketoacidosis a Rare Complication of Fibrocalculous Pancreatic Diabetes - Henny Tannady Tan; Suzanna Ndrah (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2014)
Abstract In a tropical country a case of ketosis resistant insulin dependent diabetes mellitus occurred in young lean patient who also shows evidence of malnutrition and pancreatic calculi with or without fibrosis and intermittent abdominal pain could be regarded as Fibrocalculous Pancreatic Diabetes (FCPD). We reported of a 24 years old female patient with shortness of breath since one day before she was admitted to the hospital. She also had a fever with sore throat and recurrent abdominal pain. Patient had history of abdominal pain, at that time she also developed white stools. She had a two years history of generalized body weakness associated with progressive weight lost, polydipsia and polyuria.Physical examination revealed a young lady with a low Body Mass Index (BMI) and tonsilopharyngitis. The haematological examination shown hyperglycemia, ketoacidosis, and leukocytosis. The abdominal x ray and ultrasound scan showed pancreatic calcification. The classical clinical picture of FCPD is primarily of a young diabetic patient presenting with recurrent epigastric pain, steatorrhoea, signs of malnutrition and micronutrient deficiencies. Although this case caused by ketoacidosis resistant, under special circumstances particularly after stress for example infection, trauma, etc ketosis could also be occurred.Key word: ketoacidosis, complication, fibrocalculous pancreatic diabetes Abstrak Di negara tropis, kasus resistensi terhadap ketosis yang terjadi pada pasien diabetes mellitus tipe 1 (DMT1) berusia muda, bertubuh kurus, dan disertai penyulit berupa malnutrisi dan batu pankreas dengan atau tanpa fibrosis dan nyeri abdomen intermiten, dapat disebut sebagai Diabetes Melitus Terkait Malnutrisi (DMTM). Dilaporkan kasus seorang perempuan berusia 24 tahun dengan keluhan utama sesak nafas sejak 1 hari sebelum masuk RS. Keluhan juga disertai demam, sakit tenggorokan dan nyeri abdomen berulang disertai steatorroae. Sejak 2 tahun ini ia merasa badan lemas dengan penurunan berat badan progresif, polidipsi dan poliuri. Pemeriksaan fisik didapatkan Indeks Massa Tubuh (IMT) rendah dan tonsilofaringitis. Hasil laboratorium menunjukkan hiperglikemia, ketoasidosis, dan leukositosis. Foto polos dan USG abdomen menunjukan adanya kalsifikasi pankreas. Gambaran klasik dari DMTM adalah pasien DM muda dengan gejala nyeri epigastrium berulang, steatorroea, tanda-tanda malnutrisi dan defisiensi mikronutrien. Walaupun kasus ini disebabkan oleh resistensi terhadap ketoasidosis, namun pada kasus tertentu dengan penyulit seperti infeksi, trauma, dan sebab lainnya, ketosis dapat terjadi. Kata kunci: ketoasidosis, komplikasi, Diabetes terkait Malnutrisi